Accretion processes in star formation - Hartmann, Lee 1950- (Cambridge astrophysics, 2009)
Our understanding of the formation of stars and planetary systems has changed greatly since the first edition of this book was published. This new edition has been thoroughly updated, and now includes material on molecular clouds, binaries, star clusters and the stellar initial mass function (IMF), disk evolution and planet formation. This book provides a comprehensive picture of the formation of stars and planetary systems, from their beginnings in cold clouds of molecular gas to their emergence as new suns with planet-forming disks. At each stage gravity induces an inward accretion of mass, and this is a central theme for the book. The author brings together current observations, rigorous treatments of the relevant astrophysics, and 150 illustrations, to clarify the sequence of events in star and planet formation. It is a comprehensive account of the underlying physical processes of accretion for graduate students and researchers